Generic Qualitative Research In Management Studies - Adi Susilo Jahja; Subramaniam Sri Ramalu; Mohd Shahril Ahmad Razimi (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2021)
Although qualitative research becomes more widely accepted, however, its role in management studies is still underrepresented. This is because qualitative research requires an understanding of philosophy, terminology and theories which often presents conflicting perspectives. However, it should be noted that various qualitative research approaches started with generic qualitative research, which was considered easier to implement. Therefore, this article is aimed to provide insight into generic qualitative research and explain how to do it.